2015
DOI: 10.1039/c4ra08753d
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic cooperation effect of metal nanomaterials at Au–TiO2–Ag interface to enhance photovoltaic performance for dye-sensitized solar cells

Abstract: Au and Ag nanoparticles enhance the electric energy conversion by strong plasmonic cooperation effect and complementary light absorption.Due to plasmonic cooperation effect of metal nanomaterials at Au-TiO 2 -Ag interface, Au and Ag utilized the complementary light-harvesting to enhance photovoltaic performance in dye-sensitized solar cells (DSSC). The best efficiency (η) of DSSC reached to 7.51% comparing with that of pure TiO 2 electrode (6.23%). The average energy conversion efficiency and photocurrent dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…According to the relationship τ n(EIS) = R ct × C μ1 , τ n(EIS) shows an increasing trend, which is consistent with the results of the IMVS results shown in Figure a. This might be explained by the fact that the Au nanoparticles incorporated into TiO 2 microspheres could reduce the recombination rate as a result of the better charge separation . In contrast, η c is slightly affected by the variation of Au added (Figure b) as the thin film thickness becomes the significant factor in determining electron collection …”
Section: Resultsmentioning
confidence: 99%
“…According to the relationship τ n(EIS) = R ct × C μ1 , τ n(EIS) shows an increasing trend, which is consistent with the results of the IMVS results shown in Figure a. This might be explained by the fact that the Au nanoparticles incorporated into TiO 2 microspheres could reduce the recombination rate as a result of the better charge separation . In contrast, η c is slightly affected by the variation of Au added (Figure b) as the thin film thickness becomes the significant factor in determining electron collection …”
Section: Resultsmentioning
confidence: 99%
“…The photovoltaic parameters were 18.11 AE 0.55 mA cm À2 , 0.79 AE 0.01 V, 0.70 AE 0.02, and 10.5 AE 0.3%, respectively. 33,34 The calculated electron lifetime was 7.49 ms for the DSSCs based on the photoactive lm of TiO 2 NPs with and without a panchromatic quasi-monolayer of Ag NPs between the layer of TiO 2 NPs and the scattering layer. It is concluded that the DSSCs including a quasi-monolayer of three kinds of Ag NPs are more effective for light harvesting than the DSSCs including that of a single kind of Ag NPs or conventional DSSCs.…”
Section: Resultsmentioning
confidence: 99%
“…For the DSSC including a quasi-monolayer consisting of three kinds of Ag NPs, the photovoltaic parameters were 19.27 AE 0.53 mA cm À2 , 0.79 AE 0.03 V, 0.71 AE 0.03, and 11.0 AE 0.4%, respectively. 33,34 Where R w , R k , L, and k eff represent the resistance of electron transport in the photoanode, the resistance of charge transfer related to recombination, the thickness of the photoanode, and the constant of effective rate for recombination, respectively. The open-circuit voltages and ll factor are not changed signicantly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The LSPR phenomenon is induced by collective oscillation of electrons, so when the light is incident to the noble metal nanoparticles, such as Ag or Au, the visible light is simultaneously absorbed and scattered. [22][23][24] The charging effect causes the fermi-level of the semiconductor to negatively-shift favorably to the open circuit voltage (Voc), and the plasmonic effect enhances the light absorption related to the short-circuit current density (Jsc) by extending the light path. 17,18 Because of the observed extinction property (absorption + scattering), plasmonic nanoparticles have often been used in solar cells [19][20][21] or photocatalysts to enhance performance.…”
Section: Introductionmentioning
confidence: 99%